Lingua Franca and Information Technology in Foreign Language Acquisition: Competitive Advantages of Multilingual Instruction - Turashbek, Ye.; Mazhitayeva, Sh.; Shapauov, A.; Shakhanova, R.; Sateyeva, B.; Aldazharova, A.; Zavyalova, N.; Molchanova, I.; Bogatyreva, S. (Theory and Practice in Language Studies, 2023)
The paper describes digital strategies helping to boost the competitiveness of Russian as a foreign language. The authors argue that it is impossible to deny the universal popularity of the English language. Knowledge of English is important to learners of Russian as a foreign language since it functions as a social language facilitating their transition to multilingualism. Thus, to improve the competitiveness of Russian courses, it is beneficial to supplement them with instructions in English and modern online tools with English interfaces. The paper offers two scenarios of in-class activities for beginner and intermediate-to-advanced learners of Russian, featuring key strategies utilized for students from Kazakhstan and the People’s Republic of China. The authors argue that the described activities are also useful for students from other countries. The scenarios are included in the common framework of the “Working for a Russian Digital Company” business game and enhance the competitive advantages of Russian studies programs expanding the limits of teaching language and culture in the field of online technologies and Java programming basics.
Keywords: English for special purposes; Russian as a foreign language; learning a lingua franca; online tools; business game